The meaning and significance of intercessory prayer for the Christian - Young, Ernlé W D (Rhodes University, Faculty of Divinity, Department of Divinity, 1964)
[From Introduction] 'It is a difficult and even formidable thing to write on prayer, and one fears to touch the Ark. Perhaps no one ought to undertake it unless he has spent more toil in the practice of prayer than on its principle. But perhaps also the effort to look into its principle may be graciously regarded by Him who ever liveth to make intercession as itself a prayer to know better how to pray'. So wrote P.T.Forsyth in the opening chapter of his work on prayer, 1, and at the outset of this study of the meaning and significance of Christian intercession one finds oneself echoing and endorsing his words. Intercession, of course, is only a single aspect of a far greater whole. The whole, to use Francis Thompson's phrase, is a 'many-splendoured thing'. No attempt to define and designate the limits of each of the elements which together make up prayer in its Christian fulness has ever been either entirely satisfactory or generally acceptable. But roughly speaking, there are seven colours on the palette of prayer or, to change the metaphor for one used by Leslie Weatherhead, 2, there are seven rooms in the house of prayer : Affirmation or Invocation of the Divine Presence; Adoration and Praise; Confession and the penitent seeking of Forgiveness, with the Positive Affirmation and Reception of that Forgiveness; Thanksgiving; Petition; Intercession; and Meditation. There are as well the more mystical forms of prayer admirably analysed and distinguished, for example, by Bede Frost.3. In practice, no element can be isolated or divorced from the other elements which with it make up the whole. Affirmation of God's presence issues quite naturally in adoration, which in turn leads spontaneously into confession, and so on. Each aspect of prayer acts and reacts on the others. To single out Intercession (and, insofar as it is related to it, Petition) and to write on it alone would therefore seem to require some explanation.
Keywords: Prayer; Intercessory prayer; Intercessory prayer -- Christianity